How does future climatic uncertainty affect multi-objective building energy retrofit decisions? Evidence from residential buildings in subtropical Hong Kong. (May 2023) - Liu, Sheng; Wang, Yuyang; Liu, Xiao; Yang, Linchuan; Zhang, Yingzi; He, Jingtang
Highlights: Effects of future climatic uncertainties on building retrofit decisions are estimated. Life-cycle economics and carbon emissions are selected as the multiple objectives. Future climatic uncertainties alter optimal values of some building retrofit measures. Optimal infiltration standard and insulation options are susceptible to future climate. Optimal glazing materials and shading options are not susceptible to future climate. Abstract : Energy consumption of and carbon emissions from buildings, which substantially depend on outdoor climate conditions, may be susceptible to future climate change. However, how future climatic uncertainties affect decision-making regarding building energy retrofits is unclear from the life-cycle analysis perspective. This study used typical high-rise public rental housing buildings in subtropical Hong Kong as a case study to consider future climatic uncertainties under representative concentration pathway scenarios and in different general circulation models to estimate their effect on multi-objective building retrofit decisions considering trade-offs among different objectives, namely, life-cycle economics, life-cycle carbon emissions, and operational energy use impacts. The results indicate the significant influence of future climatic uncertainties on the optimal values of building energy retrofit measures. The passive house infiltration standard and thick (0.06–0.1 m) polyurethane foam insulation can be recommended for long-term future climatic conditions (RCP8.5–2065s). By contrast, optimal values of glazing materials, horizontal shading projection factors, and window-to-wall ratio are not susceptible to future climatic uncertainties. Uncertainties from different general circulation models are another notable factor affecting optimal values and retrofit options. This study reveals the importance of considering future climatic uncertainties when deciding optimal values and selecting building energy retrofit options.